Teachers’ Attitudes towards Task-Based Language Teaching in an EFL Context - Muhammet Öcel; Ayfer Su Bergil (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The task-based language teaching approach is an indispensable part of English language teaching and has long been studied in the field of English Language Teaching. In the current English curriculum, this approach is adopted by the Ministry of National Education in Turkey. However, the studies on task-based language teaching in Turkey have not been at the desired level, yet. The main purpose of this study is to reveal teachers’ attitudes towards task-based language teaching and the reason why they implement it in their teaching or not. Accordingly, the data was collected and analyzed by using quantitative research methods. The sample of the study was composed of 130 teachers working in state schools and universities in Turkey, and all of them were administrated a questionnaire consisting of Likert-type and multiple-choice items. The overall findings of the study showed that most of the teachers have positive attitudes about task-based language teaching methods and they used it in their teaching although some of them did not use task-based language teaching because of certain factors. In addition, this study will motivate further researchers to make larger extent and practical studies that will make the authorities of the Ministry of Education and the academics in the field of English Language Teaching deeply understand the importance and the obstacles in implementing task-based language teaching.